2005
DOI: 10.1093/jxb/eri044
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of carbon dioxide, temperature, and ultraviolet-B radiation on soybean (Glycine max L.) flower and pollen morphology, pollen production, germination, and tube lengths

Abstract: Plant reproduction is highly vulnerable to global climate change components such as carbon dioxide concentration ([CO(2)]), temperature (T), and ultraviolet-B (UV-B) radiation. The objectives of this study were to determine the effects of season-long exposure to treatments of [CO(2)] at 360 (control) and 720 micromol mol(-1) (+CO(2)), temperature at 30/22 degrees C (control) and 38/30 degrees C (+T) and UV-B radiation 0 (control) and 10 kJ m(-2) d(-1) (+UV-B) on flower and pollen morphology, pollen production,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
136
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(154 citation statements)
references
References 43 publications
9
136
0
6
Order By: Relevance
“…Higher percentages of abnormal forms (>3% after Foster & Afonin, 2005) cannot be explained by natural variation and it requires external mutagen factors. Such factor are basically environmental (hydric stress, high temperature, increased CO2 atmospheric content; Mulcahy, 1981;Koti et al, 2005), pollution (heavy metal, acid rain; Visscher et al, 2004;Foster & Afonin, 2005) and UV-B radiation (stratospheric ozone destruction). Filipiak & Racki (2010) invoked the volcanic activity as a potential source of mutation leading to an abnormal palynological association in the uppermost Famennian from the Holy Cross Mountains.…”
Section: A Disturbed End-devonian Palynofloral Eventmentioning
confidence: 99%
“…Higher percentages of abnormal forms (>3% after Foster & Afonin, 2005) cannot be explained by natural variation and it requires external mutagen factors. Such factor are basically environmental (hydric stress, high temperature, increased CO2 atmospheric content; Mulcahy, 1981;Koti et al, 2005), pollution (heavy metal, acid rain; Visscher et al, 2004;Foster & Afonin, 2005) and UV-B radiation (stratospheric ozone destruction). Filipiak & Racki (2010) invoked the volcanic activity as a potential source of mutation leading to an abnormal palynological association in the uppermost Famennian from the Holy Cross Mountains.…”
Section: A Disturbed End-devonian Palynofloral Eventmentioning
confidence: 99%
“…Intra-specific variability has indeed been extensively reported in cultivated plant species for many reproductive characteristics. Genotype-specific responses have been reported for stress applied during microsporogenesis affecting carbohydrate metabolism, degeneration of the tapetal tissues, pollen wall architecture, pollen morphology, pollen viability, anther dehiscence and pollen production (Aloni et al, 2001;Koti et al, 2005;Oliver et al, 2005;Porch and Jahn, 2001;Prasad et al, 2006;Pressman et al, 2002;Srinivasan et al, 1999;Suzuki et al, 2001). At the post-anthesis level, pollen germination (Hedhly et al, 2005a;Kakani et al, 2002Kakani et al, , 2005, pollen tube growth rate (Clarke and Siddique, 2004;Hedhly et al, 2004;Srinivasan et al, 1999), and pollen dynamics (Hedhly et al, 2005a) also show genotype-specific responses.…”
Section: Genetic Variation In the Reproductive Processes Under Tempermentioning
confidence: 99%
“…Halterlein et al (1980) reported that pollen viability in common bean decreased when temperatures were held at 35/20˚C or 35˚C for a 24 h period just before anthesis. Shrunken pollen was observed at 38/30˚C in heat tolerant soybean (Glycine max L.) (Koti et al 2005).…”
Section: Introductionmentioning
confidence: 99%